THE CHALLENGES OF SCHOOL INCLUSION IN THE CLASSROOM CONTEXT - Ferreira, Mônica Cristina Camargo; Rosa, Paula Nayara Nunes; Souza, Erika Patrícia Lacerda Dias; do Carmo, Marciléia Pereira; Motta, Mireli Aparecida Santos; Marinho, Gilva Miranda (Seven Editora, 2025)
School inclusion has become a central topic in educational discussions in recent decades, driven by legislation and public policies that ensure the universal right to education. However, implementing this process faces significant challenges, especially in the classroom. This article analyzes the main obstacles related to teacher training, school infrastructure, and social attitudes, as well as successful practices that promote inclusion. It concludes that building an inclusive school culture requires collective effort, pedagogical planning, and ethical commitment from the entire school community.DOI: https://doi.org/10.56238/sevened2025.038-007